Serrated polyps in colorectal cancer prevention: prevalence, characteristics and clinical insights from a large retrospective cohort study - Fadi Abu Baker; Oren Gal; Mifleh Tatour; Baruch Ovadia; Dorin Nicola; Randa Taher; Rawi Hazzan (BMC Gastroenterology)
Abstract Background Colorectal carcinoma (CRC) screening has historically centered on the detection and removal of adenomas; however, serrated polyps, particularly sessile serrated polyps (SSPs), are increasingly acknowledged as pivotal contributors to CRC pathogenesis. This study comprehensively evaluates the prevalence, morphological characteristics, and clinical significance of serrated polyps. Methods A retrospective analysis of colonoscopies (2017–2022) was performed. Detailed demographic, clinical, endoscopic, and pathological data were reviewed, comparing serrated polyps with adenomas and hyperplastic polyps in terms of prevalence, morphology, size, location, and dysplasia. Results Among 22,175 colonoscopies, 5,836 polypectomies met inclusion criteria. Serrated polyps comprised 3.0% of all polyps and were predominantly proximal (88.5%) and flat (24.4%), with high-grade dysplasia in 21.3%. The mean age of patients with serrated polyps was 54.6 ± 8.1 years, and there was a female predominance (52.9%) compared to adenomas (39.8%, p < 0.001). A trend of lower detection rates among Arabs (2.08%) compared to Jewish patients (3.25%, p = 0.072) was observed. Fecal immunochemical testing (FIT) positivity was associated with elevated adenoma detection (32.3%) but not serrated polyp detection (3.2%). Conclusions This study highlights our practice’s low detection rate of serrated polyps, emphasizing the need for increased awareness and improved diagnostic practices. The high prevalence of flat lesions and elevated rates of dysplasia underscore the critical role they play in the prevention of CRC. The observed potential ethnic disparities and limitations of FIT suggest the need for targeted efforts to enhance detection and management practices.